Radium isotope (223Ra, 224Ra, 226Ra and 228Ra) distribution near Brazil's largest port, Paranaguá Bay, Brazil. Issue 1 (15th October 2016) - Dias, Thais H.; de Oliveira, Joselene; Sanders, Christian J.; Carvalho, Franciane; Sanders, Luciana M.; Machado, Eunice C.; Sá, Fabian
Abstract: This work investigates the 223 Ra, 224 Ra, 226 Ra and 228 Ra isotope distribution in river, estuarine waters and sediments of the Paranaguá Estuarine Complex (PEC). The stratification of the Ra isotopes along water columns indicate differing natural sources. In sediments, the radium isotope activities was inversely proportional to the particle size. The highest concentrations of 223 Ra, 224 Ra, 226 Ra and 228 Ra in the water column were found in the bottom more saline waters and towards the inner of the estuary. These relatively high concentrations towards the bottom of the estuary may be attributed to the influence of tidally driven groundwater source and desorption from particles at the maximum turbidity zone. The apparent river water ages from the radium isotope ratios, 223 Ra/ 224 Ra and 223 Ra/ 228 Ra, indicate that the principal rivers that flow into the estuary have residence times from between 6 and 11 days. Highlights: Radium isotope concentrations were evaluated along a large estuarine system. The radioactivity level in river, estuary and sediments was within a normal range. Spatial distributions of site specific radionuclides have differing activities and sources.